Fenda cervical mediana - Tagliarini, José Vicente [UNESP]; Castilho, Emanuel C. [UNESP]; Montovani, Jair Cortez [UNESP] (FapUNIFESP (SciELO), 2004)
The midline cervical cleft is an unusual congenital anomaly of the ventral neck and fewer than 100 cases have been reported overall and the first described by Bailey in 1924. This anomaly is report in association with median cleft of lower lip, cleft mandible and tongue, and hypoplasia of other midline neck structures. Its considered an anomaly originated from the two first branchial arches. The treatment of this cleft is a vertical complete excision and a closure with multiple Z-plasty. Many authors recommend avoid linear closure and prefer multiple Z-plasty for evicted fibrosis and local retraction. In this paper we report 2 case of this anomaly and the literature is reviewed.
Midline cervical cleft
Keywords: Abnormalities; Branchial region; Surgery; branchial arch; case report; cleft lip; cleft mandible; female; fibrosis; head and neck malformation; head and neck surgery; human; hypoplasia; infant; jaw malformation; male; midline cervical cleft; plastic surgery; tissue retraction; tongue disease; tongue duplication; Z plasty